Os Gestores, as empresas, e as estratégias empreendedoras: O caso das empresas industriais e da construção na região do Vale do Sousa - Duarte, Nelson (2014)
In the present paper, entrepreneurship strategies and its relations with managers and management are analysed in order to evaluate who are the real entrepreneurs. This study was done in a region of northern Portugal (Vale do Sousa) and focus on Industrial and Construction sectors. The region is composed of six concelhos in some of which it is possible to identify some industrial districts. In order to get a valid sample, a group of 251 firms were analysed. The results present a high level of risk aversion and some findings that go with literature on innovation, such as higher levels of education lead to more innovative managers, or young managers are more innovative. It was concluded, that those managers that were able to search and explore opportunities in the past, present better levels of entrepreneurship in their firms.